Pengembangan Modul Pembelajaran Fisika Berbasis Kontekstual Pada Materi Dinamika Rotasi Dan Kesetimbangan Benda Tegar - Sapiruddin -; Tarpin Juandi; Muh. Juaini (Universitas Hamzanwadi, 2019)
This research aims to develop and determine the quality of physics learning modules based on contextual on the material of rigid dynamics of rotation and equilibrium for class XI students. The research method used is the Research and Development (R & D) method which includes; analysis of potential and problems, data collection, product design, design validation, design revisions, product trials, product revisions, and usage tests. The data in this research were analyzed qualitatively deskriptive. The subject of this research included three lecturers and two physics teachers as experts, as well as students of class XI IPA MA NW Kotaraja. The research instrument used was the validation sheet and student response sheet. Design validation resulted in a score of 3.29, a product trial yielded a score of 3.17, and a trial of use resulted in a score of 3.23. All the results of this research indicate that the module is very feasible to develop.